Gender Bias Communication Among Santris in Pesantren - Nurhidayah, Yayah Yayah; Nurhayati, Eti (PALASTREN: Jurnal Studi Gender, 2020)
For decades, there has been a biased pattern of communication between genders in society, including among the Al-Ishlah santris (students) in pesantren (Islamic boarding school) in Cirebon - West Java, subject studied by the writers. The communication of male and female santris has unique ways. From the beginning, pesantren offers the different treatment to male and female santris, both in rules, ethics, sanctions, communication, and relationships in general. In addition, the teaching of classic kitabs (books/holy books) still contains a lot of gender biases. This study aims to identify several gender biases and stereotypes in various forms of communication between male and female santris in pesantren. This research used descriptive qualitative methods, data collection techniques using interviews and observations to santris, and data analysis techniques carried out qualitatively in the form of narrative descriptions. The results of the study show there are many gender biases and stereotypes in various forms of communication, such as: communication style, conversation initiatives, intensity of conducting conversation, intensity of interruption, dominance in conversation, intensity of making humor, eye contact, spatial distance, body language, smile, and touch.Keywords: communication, gender bias, pesantren